1995
DOI: 10.1002/ar.1092410305
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric evaluation of volume shifts between intra‐ and extra‐cellular space before and during global ischemia

Abstract: Cellular and interstitial alterations seen at the onset and during the course of ischemia are dependent upon the method of cardiac arrest. Furthermore, a considerable mutual influence is exerted by the alterations in cellular and interstitial spaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…22 A number of previous reports had also shown that the volumes of both plasmatic and interstitial fluids were decreased in ischemia. [22][23][24][25][26][27] This shrinkage of the overall extracellular fluid is, therefore, presumably the reason why interstitial distribution volume of DTPA: (1) was found to depend on coronary flow rates and (2) was reduced in our ischemic experiments. This hypothesis is strengthened by the additional observation that the water content of hearts, determined at the end of experiments, was lower in ischemic than in normoxic experiments.…”
Section: Myocardial Kinetics Of Dtpa In Low-flow Ischemiamentioning
confidence: 84%
“…22 A number of previous reports had also shown that the volumes of both plasmatic and interstitial fluids were decreased in ischemia. [22][23][24][25][26][27] This shrinkage of the overall extracellular fluid is, therefore, presumably the reason why interstitial distribution volume of DTPA: (1) was found to depend on coronary flow rates and (2) was reduced in our ischemic experiments. This hypothesis is strengthened by the additional observation that the water content of hearts, determined at the end of experiments, was lower in ischemic than in normoxic experiments.…”
Section: Myocardial Kinetics Of Dtpa In Low-flow Ischemiamentioning
confidence: 84%
“…Tissue edema is a consequence of reperfusion injury and is known to interfere with electrical conduction, oxygenation, and both systolic and diastolic myocardial function . We used MRI to assess both the magnitude of extracellular water and its effect on tissue structure and order.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue edema is a consequence of reperfusion injury and is known to interfere with electrical conduction, 18 oxygenation, 19 and both systolic and diastolic myocardial function. [20][21][22] We used MRI to assess both the magnitude of extracellular water and its effect on tissue structure and order. The increase in T 2 signal may reflect both an absolute increase in water and/or a change in the extent of hydration status of primarily structural proteins such as collagen.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of myocardial ultrastructure by quantifying different degrees of ischemic injury was applied by several authors (DiBona and Powell, 1980;Schmiedl et al, 1995). It was shown that the swelling of mitochondria and cardiomyocytes, respectively, is closely correlated with the functional status of the ischemic heart (Murry et al, 1990;Gorge et al, 1991).…”
Section: Discussionmentioning
confidence: 99%